2023
DOI: 10.1038/s41588-023-01375-1
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analyses and host genetics highlight the role of innate immune cells in COVID-19 severity

Abstract: Mechanisms underpinning the dysfunctional immune response in severe acute respiratory syndrome coronavirus 2 infection are elusive. We analyzed single-cell transcriptomes and T and B cell receptors (BCR) of >895,000 peripheral blood mononuclear cells from 73 coronavirus disease 2019 (COVID-19) patients and 75 healthy controls of Japanese ancestry with host genetic data. COVID-19 patients showed a low fraction of nonclassical monocytes (ncMono). We report downregulated cell transitions from classical monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 64 publications
(116 reference statements)
0
8
0
Order By: Relevance
“…Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which initially targets the epithelial tissue of the nasal cavity and spreads to the upper respiratory tract, lung, and other organs. Here, we utilized BCR heavy chain data from a single cell sequencing study of primary blood mononuclear cells (PBMCs) of 44 COVID-19 patients (106,640 BCRs) and 58 healthy donors (174,139 BCRs), all of whom were unvaccinated 31 . After splitting the randomly, 71 donors were used for training and 31 were held out for testing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which initially targets the epithelial tissue of the nasal cavity and spreads to the upper respiratory tract, lung, and other organs. Here, we utilized BCR heavy chain data from a single cell sequencing study of primary blood mononuclear cells (PBMCs) of 44 COVID-19 patients (106,640 BCRs) and 58 healthy donors (174,139 BCRs), all of whom were unvaccinated 31 . After splitting the randomly, 71 donors were used for training and 31 were held out for testing.…”
Section: Resultsmentioning
confidence: 99%
“…1A ) and paratope ( Fig. 1B ) networks using the BCRs of ten COVID-19 from a previous study 30 . Notably, none of the clonotype networks connected different donors, consistent with the previously reported low sharing of BCR clones 9, 22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have identified specific genetic variants associated with increased risk, highlighting the importance of genetic predisposition. 49 , 50 …”
Section: Discussionmentioning
confidence: 99%
“…Given that patients with severe COVID-19 exhibit substantial immune changes including lymphopenia [16][17][18], we also explored the components of the different S8A). The previous study has shown that the severe/ critical patients' antigen processing and presentation ability was significantly reduced [19], which was consistent with our result (Figure S8A).…”
Section: Single Sample Gene Set Enrichment Analysis (Ssgsea) and Gene...mentioning
confidence: 99%